EMANSIPASI PEREMPUAN VERSUS KODRAT PEREMPUAN(Telaah atas pemikiran Qasim Amin) - ABBAS, NURLAELAH (PSW, 2010)
: Qasim Aminâs opinion on his book, Tahrir Al-Marâah (woman liberation), emphasizing about a womanâs idea of liberation and shackle of discrimination and subordination. Qasim had tried to open the faucet of stopper of people progress by eliminating tradition of menfolk subordination. His method used focused a reinterpretationof al-qurâan and hadis which will always legitimate the existence of patriarkhi systems in society.Qasim Amin developed and strength the fundamental idea in previous masterpiece when woman have more or less brightened with the liberation idea hence Qasim Amin started to fight for the woman enableness.According to him, woman have to behave full self-supporting without having to depend on menfolk.